Nivel de conocimientos, actitudes y practicas sobre lactancia materna exclusiva en madres de edad fértil que acuden al Centro de Salud Alfredo Baquerizo Moreno, Jujan-Guayas, octubre 2018- abril 2019 - Campuzano Bravo, Carla Estefania (2019)
The present investigative work is about the fact that the Alfredo Baquerizo Moreno Health Center does not include statistical data on exclusive breastfeeding, and for which this study was conducted on the level of knowledge, attitudes and practices on exclusive breastfeeding Objective: To identify the levels of knowledge, attitudes and practices on exclusive breastfeeding in mothers of fertile age who attend the Alfredo Baquerizo Moreno Health Center, Jujan-Guayas, October 2018 - April 2019 Methodology: It is a descriptive, observational, non-experimental cross-sectional study. We interviewed 130 mothers who attended the health center Alfredo Baquerizo Moreno, through a questionnaire with 15 items, divided into 3 sections of knowledge, attitudes, practice on breastfeeding. Results: It was found that 27% of the surveyed mothers know about exclusive breastfeeding, 23% know the benefits for the baby, 23% of the mothers indicated that they would not give anything before 6 months to the baby and only 23% perform a correct breastfeeding technique. Conclusion: In the process it was evidenced that most of the mothers surveyed 60% have a low level of knowledge, followed by 69% of mothers with a low level of attitude in relation to breastfeeding and finally it is alarming that almost all mothers 64% mothers do not have a good practice when breastfeeding for it means that it is low level of breastfeeding practices.